Excimer formation by stacking G-quadruplex blocks - Dao, Nguyen Thuan (2014)
A special stack: In the presence of K+ ions, a specific guanine-rich DNA sequence forms a stacked G-quadruplex dimer giving rise to excimer emission in the 400 nm region. This emission with nanosecond lifetime occurs only for a particular base overlap pattern between two stacked G-quadruplex blocks and can be manipulated by changing DNA sequence and external conditions.